2013
DOI: 10.1590/s2317-64312013000300007
|View full text |Cite
|
Sign up to set email alerts
|

Estéreos pessoais: hábitos auditivos e avaliação audiológica

Abstract: OBJETIVO: Caracterizar os hábitos auditivos e relacioná-los aos achados audiológicos de adultos sem queixas auditivas, usuários de estéreos pessoais. MÉTODOS: Foram avaliados 85 indivíduos, com idades entre 18 e 34 anos, com audição normal, sem exposição a ruído ocupacional. Todos responderam a um questionário de hábitos auditivos, disponibilizado na Internet e foram convocados para a avaliação audiológica: Audiometria Altas Frequências, Emissões Otoacústicas Evocadas por Estímulo Transiente (EOAT) e Emissões … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
7

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 20 publications
1
10
0
7
Order By: Relevance
“…Data on concern about hearing health proved to be in line with the findings of a study 38 conducted in the United States (USA), yet the data disagreed with another study 1 conducted in Brazil, where most care about hearing health and believe that bad habits can damage hearing.…”
Section: Faria and Mellomentioning
confidence: 66%
See 2 more Smart Citations
“…Data on concern about hearing health proved to be in line with the findings of a study 38 conducted in the United States (USA), yet the data disagreed with another study 1 conducted in Brazil, where most care about hearing health and believe that bad habits can damage hearing.…”
Section: Faria and Mellomentioning
confidence: 66%
“…However, not everyone knows that excessive use of these devices may cause irreversible damage to hearing 1 , in the short or long term 2 . This habit, when frequent, added to the exposure time, the physical characteristics (such as frequency and intensity), and other non-occupational noise at high sound levels, determines the impact on hearing health, and results in a public health problem, which affects most of the world population [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This abusive use with high duration, intensity and/or frequency of exposure to music may lead to auditory function disorders [3][4][5][6] and it may cause severe consequences to life quality 7 . The occurrence of auditory symptoms such as hypoacusis, ear fullness or dizziness and tinnitus after using personal stereos may suggest higher risks to young people's hearing 5,6,8 . It indicates a relationship among these symptoms and the habit of using personal stereos 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight that tinnitus may cause concentration, sleep and learning interference, becoming an important symptom to be investigated, because it is common in this population 3 . According to a recent study, as longer is the time of headsets use, higher is the tinnitus occurrence 6 . Besides, another study observed that people with tinnitus may present alteration of medial olivocochlear tract function, observed through lower otoacoustic emissions suppression 14 .…”
Section: Introductionmentioning
confidence: 99%